2001
DOI: 10.1161/01.atv.21.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Extracellular Adenosine Levels by Vascular Smooth Muscle Cells From Spontaneously Hypertensive Rats

Abstract: Abstract-The objective of this investigation was to determine whether the regulation of extracellular adenosine levels by smooth muscle cells (SMCs) from conduit arteries (aorta) and resistance microvessels (renal arterioles) is different in spontaneously hypertensive rats (SHR) versus normotensive Wistar-Kyoto (WKY) rats. Basal extracellular adenosine levels were decreased in cultured aortic and arteriolar SHR SMCs, and the increase in extracellular adenosine levels induced by stimulation of the cAMP-adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…With regard to major purine-inactivating pathways, ADA and CD73 were remarkably active in both control and diabetic VSMCs, with no residual AMP or adenosine found in the medium 24 h after supplementation. We also found a tendency to increased inosine generation following adenosine supplementation by diabetic VSMCs, possibly as a result of increased ADA activity, as described in diabetic patients [ 43 ] and in experimental models of hypertension [ 44 ]. Residual inosine concentrations following inosine supplementation to diabetic VSMCs were also higher than in control VSMCs.…”
Section: Discussionsupporting
confidence: 64%
“…With regard to major purine-inactivating pathways, ADA and CD73 were remarkably active in both control and diabetic VSMCs, with no residual AMP or adenosine found in the medium 24 h after supplementation. We also found a tendency to increased inosine generation following adenosine supplementation by diabetic VSMCs, possibly as a result of increased ADA activity, as described in diabetic patients [ 43 ] and in experimental models of hypertension [ 44 ]. Residual inosine concentrations following inosine supplementation to diabetic VSMCs were also higher than in control VSMCs.…”
Section: Discussionsupporting
confidence: 64%
“…For example, hypertrophic myocardium is intolerant of ischemic and other forms of insult, likely for multiple reasons. Not only is adenosine potentially involved in regulating cardiac and vascular hypertrophic growth (66)(67)(68)(69), but also adenosinergic signaling is modified in hypertrophic tissue (204,273,307). Whether such changes contribute to the intolerant phenotypes remains to be directly tested.…”
Section: "Dysregulation" Of Adenosinergic Cardioprotectionmentioning
confidence: 99%
“…Whether such changes contribute to the intolerant phenotypes remains to be directly tested. However, adenosinergic therapy has been shown to counter detrimental phenotypic changes associated with hypertrophy (39), dysregulation of adenosine formation may occur in hypertrophy (53), and dysregulation of adenosine formation with hypertension is involved in modifying vascular proliferation (69). There is therefore good evidence that cardiovascular responses to these disease states are associated with altered adenosine signaling and/or protection.…”
Section: "Dysregulation" Of Adenosinergic Cardioprotectionmentioning
confidence: 99%
“…5 Adenosine is a potent regulator of growth in both vascular and nonvascular cells. 6 -8 We have previously shown that adenosine inhibits growth of renal arteriolar 9 and aortic smooth muscle 6 cells, which play a key role in vascular remodeling leading to vaso-occlusive disorders. Moreover, using receptor-specific agonists and antagonists as well as antisense oligonucleotides, we demonstrated that the antimitogenic effects of adenosine are mediated by activation of A 2B receptors.…”
mentioning
confidence: 99%